Art for Marketing, Marketing for the Arts: A 30‐Year‐Long Relationship via the Art‐based management perspective - Masè, Stefania; Cedrola, Elena; Cohen‐Cheminet, Genevieve; Sharma, Piyush (2019)
Recent research highlights the increasing importance of the arts as a management resource. Since the last two decades of the last century decreasing public investments in art and culture has made the art sector more open to private funds. At the same time – and increasingly in recent years - investing in art has been a viable strategy to build cultural infrastructure favorable to strong brand image. As a burgeoning area of research, art-based management still lacks clearly defined boundaries. A systematic literature review is used here to perform as wide and comprehensive an analysis as possible of the last 30-years relationship between Art & Business to highlight all the possible ways the visual arts can sustain the implementation of successful marketing strategies. This retrospective gives a solid ground both for managers from different industries who contemplate marketing strategies referable to the art-based management framework and for art managers who consider their roles as active referents for private donations.